Spin caloritronics in armchair silicene nanoribbons with sp3 and sp2-type alternating hybridizations. (8th August 2018) - Tan, Xing-Yi; Wu, Dan-Dan; Liu, Qing-Bo; Fu, Hua-Hua; Wu, Ruqian
Abstract: Finite-layer nanoribbon materials have long been considered as potential candidates for nanodevices with novel quantum effects. Here we constructed a series of ferromagnetic armchair silicene nanoribbons (ASiNRs) with sp 3 and sp 2 -type alternating hybridizations, and found that the ASiNRs with different widths are localized in different spin-resolved electronic states. As the width parameter N is increased from 5 to 22, the ASiNR transits from indirect-gap half metallicity (HM), to indirect-gap spin semiconductor (SC), then to direct-gap SC and finally to direct-gap HM. When a temperature gradient is produced along the nanoribbons, the spin-dependent currents with the opposite flow directions are driven and a nearly perfect spin-dependent Seebeck effect (SDSE) occurs. Moreover, attributing to symmetrical spin-resolved transport channels, nearly pure thermal spin current without any accompanying charge current can be generated. In addition, for some ASiNRs with proper widths, both the thermal spin-up current and spin-down one are contributed by the electrons in energy valleys, resulting in a well-defined valley-dependent SDSE. These theoretical findings suggest that the ASiNRs with the sp 3 and sp 2 -type alternating hybridizations can be outstanding candidates for future spin caloritronic devices.